1947
DOI: 10.1017/s0007485300030509
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Chafer Grub Problem in the Lake District

Abstract: 1. The Garden Chafer (Phyllopertha horticola) causes extensive deterioration of the fell grassland in the Lake District.2. The flight period of the adult beetles occurs between the end of May and the latter end of June.3. Eggs are laid in the soil at a depth of about 2½ inches, but the depth varies according to the nature of the soil. The eggs take from 27 to 30 days to hatch in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1951
1951
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Because females normally place eggs 4-10 em deep in the soil (Fleming 1972), early first-instar Japanese beetles likely feed initially on organic matter and fine roots. This behavior pattern has been reported in other scarab species (Gray et al 1947)_ The attractive or arrestant properties of turf grass roots to Japanese beetle grubs could not be ascertained at this stage in our study. The tendency of neonate Japanese beetles to be down in the soil profile may have important ramifications on timing of insecticide treatments and sampling if first instars have not yet moved to the soil-sod interface.…”
Section: Second Instarsupporting
confidence: 39%
“…Because females normally place eggs 4-10 em deep in the soil (Fleming 1972), early first-instar Japanese beetles likely feed initially on organic matter and fine roots. This behavior pattern has been reported in other scarab species (Gray et al 1947)_ The attractive or arrestant properties of turf grass roots to Japanese beetle grubs could not be ascertained at this stage in our study. The tendency of neonate Japanese beetles to be down in the soil profile may have important ramifications on timing of insecticide treatments and sampling if first instars have not yet moved to the soil-sod interface.…”
Section: Second Instarsupporting
confidence: 39%
“…Spatial distribution of garden-chafer grubs is very patchy and irregular (Gray, Peet & Eogerson, 1947;Eaw, 1951). If the distribution in a field has been mapped by systematic sampling just before the flight season (to be dealt with in Part VIII of this series), it will be found that swarming is always confined very accurately to the infested areas of sward even when these show no obvious differences from the uninfested parts.…”
Section: Siting and Coherence Of The Swarmmentioning
confidence: 99%
“…Thomas & Heal (1944) show a detailed map of the grasslands damaged by garden chafer in North Wales during 1942-43. Gray, Peet & Eogerson (1947) do likewise for the Lake District during 1938-39. Eaw (1951) lists the major outbreak areas in Gloucestershire, Wiltshire, Somerset and Dorset during 1945-48.…”
Section: Geographical Distributionmentioning
confidence: 67%
“…No Mermithids were found in larvae from either the drier or wetter parts in any comparison of these parts. This is not surprising since Gray, Peet & Eogerson (1947) put infestation at a mere 0-54 per cent. (600 larvae examined 1938-39) while the number we ourselves encountered in much larger collections (14,860 larvae between 1948 and 1962) represented only 045 per cent.…”
Section: Enemies In the Drier And Wetter Parts Of Fell Grasslandmentioning
confidence: 99%
See 1 more Smart Citation